PENGEMBANGAN BAHAN AJAR MATERI PERSAMAAN KUADRAT BERBANTUAN RUMUS CEPAT - Nur Kesumayanti; Rizki Wahyu Yunian Putra (Department of Mathematics Education, Universitas Kuningan, 2017)
ABSTRACTThe purpose of this research is to produce material of quadratic equations supported by quick, appealing, and easy formula for students. The Method of This research is Research and Development Procedure ( R D) from Brog and Gall which is adopted by Sucipto that is up to the seventh stage, such as: potential problem, data collection, product design, design validation, design revision, product trial, and product revisions. The subject of this research is one of high school students in Bandar Lampung. The data collection was obtained from the validation of the instruments as well as trials of small group and large group products. This researchs analyzed by descriptive quantitative and qualitative. The products produced through the validation of the feasibility of the material expert validator team, the media expert, the linguist and the mathematic teacher and the language teacher obtained the criteria